2019
DOI: 10.1002/soej.12352
|View full text |Cite
|
Sign up to set email alerts
|

Higher Wages, Less Gym Time? The Effects of Minimum Wages on Time Use

Abstract: This study examines the effects of minimum wages on time use. Analyzing data from the American Time Use Survey from 2003 to 2017, I investigate the role of time allocated toward exercise and other health‐enhancing activities as a potential mechanism underlying the link between minimum wages and health. The study finds that a $1 increase in minimum wages is associated with reductions in exercising and total personal health time by 13 and 20 minutes during the week, respectively. This decline in health time is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…On the contrary, another study concluded that home production decreases when unemployment insurance benefits increase, which the authors interpreted as a substitution between the two mechanisms against loss of earnings during unemployment spells (Guler & Taskin, 2013). Still others found that increases in the minimum wage increase leisure time but decrease exercise (Lenhart, 2019). A study of macroeconomic conditions on time spent with children found that increased unemployment rates increase the amount of enriching childfather time in families with young children (Bauer & Sonchak, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, another study concluded that home production decreases when unemployment insurance benefits increase, which the authors interpreted as a substitution between the two mechanisms against loss of earnings during unemployment spells (Guler & Taskin, 2013). Still others found that increases in the minimum wage increase leisure time but decrease exercise (Lenhart, 2019). A study of macroeconomic conditions on time spent with children found that increased unemployment rates increase the amount of enriching childfather time in families with young children (Bauer & Sonchak, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In response to greater income, or greater incentives for work, one parent may specialize in earning income whereas the other may decrease work and increase the time spent with children. This may account for the pattern of increased child care time among non-employed adults found by Lenhart ( 2019 ). Further, never-married individuals and individuals of color are more likely to be minimum wage earners than their counterparts (Sawhill & Karpilow, 2014 ) and time use varies by marital and employment status (Kalil et al, 2014 ; Pepin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 75%
“…Improved resources, reduced stress, and changes in time use may be mechanisms underlying the benefits of a policy like minimum wage, but to date, little research has examined how the minimum wage affects non-employment time. One exception is Lenhart ( 2019 ), who used data from the American Time Use Survey (ATUS) to examine the effects of changes in effective state minimum wage rates on health-related time use from 2003 to 2017, finding increased leisure time, and that non-employed individuals living with children spent an additional 37 min in total time caring for children (Lenhart, 2019 ). However, the study examined only total child care time, while developmental theory and science emphasizes the importance of developmental or interactive time in enriching activities such as playing with or reading to children or helping with homework (Committee on Integrating the Science of Early Childhood Development Youth, and Families and Press, 2000 ; Kalil et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations